Prevalensi Malnutrisi Balita di Desa Karimunting, Kec. Sungai Raya, Kab. Bengkayang, Provinsi Kalimantan Barat: Malnutrition Prevalence of Toddler in Karimunting Village, Sungai Raya District, Bengkayang Regency, West Kalimantan Province - Intan Aryanti; Rachma Hidana; Yolanda Safitri; M. Ikhsan Jufri; Putrya Hawa; Dwi Monik Purnamasari; Elies Fitriani (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2022)
Indonesian children are still experiencing a double burden of malnutrition, both in undernutrition and overnutrition. Based on study, there is an intergenerational effect, such as short condition of parents as a child will affect the next generation’s growth and development and will increase the risk of cognitive delay. This result of this study is expected to help and become a reference for local and national governments in order to manage strategies for handling malnutrition and to achieve national health resilience. This research is descriptive cross-sectional study with total sampling. The study used secondary data of 322 children under 5 years old from Sungai Raya District Health Center from July-August 2021, originating from 7 unit health centre (posyandu). The data obtained in the form of age, body weight (BW), body length (BL)/height (BH) and classified according to the WHO curve (W/Age, BH/age, BW/BH) then calculate the Z score. The result showed that children under 5 yo in short and very short stature children were 13% and 19%. Children with overweight and obesity based on BW/BH in this study were 7 % and 5 %. In conclusion, there was a double burden malnutrition which exceeds the national average.